Cytomegalovirus-Induced Gastrointestinal Bleeding and Pancreatitis Complicating Severe Covid-19 Pneumonia: a Paradigmatic Case. - Giacomo Marchi; Alice Vianello; Ernesto Crisafulli; Alessio Maroccia; Stefano Francesco Crinò; Sara Pecori; Giulia A Zamboni; Fulvia Mazzaferri; Evelina Tacconelli; Domenico Girelli (Mediterranean Journal of Hematology and Infectious Diseases)
Key points: